Empirical Analysis of Impact of Social Media on Tourismthrough Branding & Promotional Strategies in India (International Journal of Food and Nutritional Sciences, 2022)
This study is based on the empirical analysis. It attempts to explore theimpact of social media on tourism through branding & promotional strategies in India. Theresearch aims to identify strategies and challenges faced by industry experts in positioning India as acompetitive tourist spotand propose areas for enhancement. The research methodologyhas various combinations of content analysis and empirical studies.The findings highlight the significance of effective positioning strategies inattracting tourists and creating economic & financial benefits. Challenges such as communication barriers, especially language andaccess to field experts were faced during the study. The studygives the scope for further research workwith the option of greater time frame to analyze in-depth issues involved in social media and its impact on tourism in India. In nutshell thisstudy contributes to understanding the implications and opportunities for increasing thebranding and promotion strategiesfor promotion of tourism in India.